2017
DOI: 10.7752/jpes.2017.s1003
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract:It is believed that sports and financial performances are linked to each other. Football clubs with weak financial performance are generally in bad positions in terms of sports success. On the other hand, there are only a limited number of football clubs which are in good financial standing without achieving serious sports success. After the increasing number of financial distress reports coming from various European football clubs and the concern about the role of external funds providers, the UEFA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
0
7
0
4
Order By: Relevance
“…On the other hand, Carmichael et al (2011) indicated how the results “on the field” are conditioned by the technical/tactical resources of the team and how the economic-financial management (more precisely the turnover) of the club can impact on these sports results. In contrast, Sakinc et al (2017) highlight a weak correlation between the two types of performance; the Spearman's correlation calculated is just 0.17 and is statistically not significant.…”
Section: Literature and Research Hypothesismentioning
confidence: 70%
“…On the other hand, Carmichael et al (2011) indicated how the results “on the field” are conditioned by the technical/tactical resources of the team and how the economic-financial management (more precisely the turnover) of the club can impact on these sports results. In contrast, Sakinc et al (2017) highlight a weak correlation between the two types of performance; the Spearman's correlation calculated is just 0.17 and is statistically not significant.…”
Section: Literature and Research Hypothesismentioning
confidence: 70%
“…In these two main approaches, it is seen that both market-based financial performance indicators and accounting-based financial performance indicators are used. In studies, stock value has come to the fore as a market-based financial performance indicator (Renneboog & Vanbrabant, 2000;Berument et al, 2006;Aygören et al, 2008;Samagaio, 2009;Putra & Wasistha, 2018) while liquidity, profitability and liabilities have come to the fore as accounting-based performance indicators (Atmaca, 2012;Karadeniz et al, 2014;Nurcan et al, 2016;Pradhan et al, 2016;Sakınç et al, 2017). In addition, research that analyzes the financial performance of football clubs often focuses on a particular league (Guzman & Morrow, 2007;Baroncelli & Caruso, 2011;Ecer & Boyukaslan, 2014;Galariotis et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In many of these studies, MCDM methods have been used for performance evaluation. Pradhan et al (2016) investigated the financial performance of Italian clubs using gray relation analysis (GRA), Galariotis et al (2018) determined the business, financial and sports performance of clubs in the French league using the PROMETHEE II method, Sakınç et al (2017) studied the financial and sporting performance of 22 European clubs using the TOPSIS method, Chelmis et al (2019) investigated the financial, commercial and sporting performance of clubs in the Greek league using PROMETHEE II and Salabun et al (2020) determined the performance of football players using the characteristic objects method (COMET) and TOPSIS method. In addition to these methods used, the most used MCDM method is DEA which was developed by Charnes et al (1978).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It does not seem realistic to evaluate these two processes independently from each other in football clubs where financial success supports sportive success. Some studies in the literature have carried out financial evaluations by only considering the financial data of clubs (Pradhan et al, 2016;Chelmis et al, 2019), some have focused only on sportive success (Rossi et al, 2019;Salabun et al2020) and others have tried to associate financial success with sportive success (Sakınç et al, 2017;Galariotis et al, 2018). However, the success of football clubs is possible with the realization of the financial and sportive success together in this cycle.…”
Section: Introductionmentioning
confidence: 99%